2020
DOI: 10.47405/mjssh.v5i10.511
|View full text |Cite
|
Sign up to set email alerts
|

Budaya Sekolah: Hubungannya dengan Komitmen Guru

Abstract: Komitmen guru amat penting bagi memastikan kemenjadian murid seperti mana dalam PPPM 2013- 2025. Kajian ini adalah untuk mengenal pasti hubungan budaya sekolah terhadap komitmen guru sekolah rendah di bahagian pedalaman atas negeri Sabah, Malaysia. Kajian berbentuk bukan jenis eksperimental ini menggunakan kaedah tinjauan dan menggabungkan tiga teknik pensampelan kebarangkalian untuk mendapatkan sampel. Dua set soal selidik iaitu TCM Employee Commitment Survey (Meyer & Allen, 2004) dan Soal Selidik Budaya … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 19 publications
0
1
0
2
Order By: Relevance
“…Female workers may also exhibit diminished affective commitment towards employers with minimal investments in human resource management practises, unlike male workers whose affective commitment is less affected by such procedures (Shin et al, 2020). The result is consistent with a previous study conducted by Billy and Taat (2020) which discovered considerable differences in teacher commitment between male and female respondents in the interior of Sabah state. The results showed that male teachers had a higher perception of teacher commitment compared to their female counterparts.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Female workers may also exhibit diminished affective commitment towards employers with minimal investments in human resource management practises, unlike male workers whose affective commitment is less affected by such procedures (Shin et al, 2020). The result is consistent with a previous study conducted by Billy and Taat (2020) which discovered considerable differences in teacher commitment between male and female respondents in the interior of Sabah state. The results showed that male teachers had a higher perception of teacher commitment compared to their female counterparts.…”
Section: Discussionsupporting
confidence: 89%
“…Based on their findings, a significant difference in organizational commitment based on gender was observed due to the leadership style demonstrated by employers, which in turn impacts the particular organization and influences employee commitment. Meanwhile, Billy and Taat (2020) examined the research findings that revealed major discrepancies in teacher commitment between male and female respondents in the interior of Sabah state. The study found that male teachers had higher perceptions of teacher commitment variables than their female counterparts, contributing to this difference.…”
mentioning
confidence: 99%
“…Sekolah yang mempunyai guru yang komited dapat meningkatkan prestasi sekolah sama ada dalam bidang akademik, kokurikulum mahupun pengurusan sekolah (Latipah & Mohd Khairuddin, 2021). Ini kerana sekolah yang mempunyai guru yang komited mempunyai sumber manusia yang bertanggungjawab terhadap pekerjaan (Billy & Taat, 2020). Komitmen organisasi ditakrifkan sebagai keinginan ahli organisasi untuk kekal sebagai ahli organisasi.…”
Section: Pengenalanunclassified
“…In an organization, "teamwork" and "network" are essential things to build in making changes (Billy & Taat, 2020). An effective work team is essential because it will deal directly with stakeholders or partners.…”
Section: Cultural Planning Spiritual Communicationmentioning
confidence: 99%